Além da metafísica e do niilismosmo: a cosmovisão trágica de Nietzsche - Moraes, Eduardo Carli de (2013)
This dissertation aims to reflect upon the philosophy of Friedrich Nietzsche (18441900), whose thought is here understood as an attempt to overcome both metaphysics and nihilism. This study highlights Nietzsche’s appraisal of philosophical thought endowed with historical sense, faithful to the uninterrupted process of becoming, which implies a worldview similar to that of Heraclitus. It is argued that Nietzsche's peculiar position in the history of moral philosophy lies in his critical analysis of the multiplicity of different moral evaluations always connected with their human, all too human, sources. Through attention to the circumstances and conditions of the emergence, development and decline of many ideals, moral values and religious doctrines, we intend to describe Nietzsche's philosophy as one in rupture with the notion of divine and immutable values and which de-estabilizes beliefs in absolute truths. In order to illustrate the nietzschean genealogical method in operation, we investigate phenomena such as resentment and asceticism, re-inserted into the historical flow and understood with connection with their physiological, psychological and socio-political basis. Grounded on extensive literature review of the work of Nietzsche and his commentators (especially Jaspers, Wotling, Rosset, Giacoia, Moura, Ferraz, among others), it is argued that Nietzsche’s philosophy surpasses Platonic-Christian split between two worlds and also overcomes the dualism between body and spirit. The anti-idealistic philosophy of Nietzsche, critical of moral absolutism and metaphysical supernaturalism, acts as a "school of suspicion" inviting us to free our thought from subservience, credulity and uncritical obedience to tradition. This research also explores the theme of “the death of God" and the collapse of the Judeo-Christian values, and the concomitant rise of nihilism, in the context of a philosophy that seeks to suggest and open new avenues for the human adventure, by mobilizing concepts such as amor fati, Over-Man and "fidelity to the earth." Nietzsche’s thought is not understood only in its critical potential, shattering traditional idealistic metaphysics, but also as a creator of a tragic and dyonisian wisdom which stands at the antipodes of both ascetic ideals and nihilistic doctrines.